A Comparison of Job Creation and Job Destruction in Canada and the United States - Baldwin, John; Dunne, Timothy; Haltiwanger, John (The Review of Economics and Statistics, 1998)
In recent years a growing number of countries have constructed data series on job creation and job destruction using establishment-level data sets. This paper provides a description and detailed comparison of these new data series for the United States and Canada. Pint, the Canadian and United States industry-level job creation and destruction rates are remarkably similar. Industries with high (low) job creation in the U.S. exhibit high (low) job creation in Canada. The same is true for job destruction. In addition, the overall magnitude of gross job flows in the two countries is comparable. Second, the time-series patterns of creation and destruction are qualitatively similar but do differ in a number of important respects. In both countries, job destruction is much more cyclically volatile than job creation. This cyclical asymmetry is, however, more pronounced in the United States. The paper finishes with a characterization of the job flow patterns using a modified